2007
DOI: 10.1093/brain/awm174
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Characteristics of orthostatic hypotension in Parkinson's disease

Abstract: Clinical symptoms of Parkinson's disease (PD) include not only motor distress but also autonomic dysfunction. Orthostatic hypotension (OH) occurs in one-fifth to one-half of all patients with PD. We examined the relation of this type of hypotension to clinical features and cardiovascular parameters such as cardiac 123I-meta-iodobenzylguanidine (MIBG) uptake, changes on the Valsalva maneuver, and plasma norepinephrine concentrations on head-up tilt-table testing (HUT). We performed HUT in 55 patients with PD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 57 publications
1
30
0
3
Order By: Relevance
“…Oka et al (125) examined the association between myocardial 123 I-MIBG uptake and orthostatic hypotension, pulse, and blood pressure changes during the Valsalva maneuver and erect and supine plasma norepinephrine concentrations in PD patients. Mean myocardial 123 I-MIBG uptake was significantly lower in PD patients with orthostatic hypotension and an abnormal Valsalva response.…”
Section: Imaging Cardiac Sympathetic Denervation In Pdmentioning
confidence: 99%
“…Oka et al (125) examined the association between myocardial 123 I-MIBG uptake and orthostatic hypotension, pulse, and blood pressure changes during the Valsalva maneuver and erect and supine plasma norepinephrine concentrations in PD patients. Mean myocardial 123 I-MIBG uptake was significantly lower in PD patients with orthostatic hypotension and an abnormal Valsalva response.…”
Section: Imaging Cardiac Sympathetic Denervation In Pdmentioning
confidence: 99%
“…For example, orthostatic hypotension is a common symptom of cardiovascular dysfunction in patients with PD, which appears to arise from a combination of vasomotor-, cardiac sympathetic-, and baroreflex-dysfunction (13). Importantly, attenuated baroreflex function in PD may even precede the behavioral and motor symptoms of PD (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Impairments of the autonomic nervous system such as OH are frequently observed in patients with PD [18,19,20]. The autonomic cardiovascular function in PD was demonstrated previously using various tests.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported that the plasma norepinephrine concentration is lower in PD patients [24]. The plasma norepinephrine concentration during standing responses is low in PD patients [18,19,24,25]. Cardiac (123)I-metaiodobenzylguanidine (123I-MIBG) is a pharmacologically inactive analogue of norepinephrine, which is similarly metabolized in noradrenergic neurons.…”
Section: Discussionmentioning
confidence: 99%